Research priority setting related to older adults: a scoping review to inform the Cochrane-Campbell Global Ageing Partnership work programme. Issue 9 (19th September 2022) - Barbeau, Victoria I; Madani, Leen; Al Ameer, Abdulah; Tanjong Ghogomu, Elizabeth; Beecher, Deirdre; Conde, Monserrat; Howe, Tracey E; Marcus, Sue; Morley, Richard; Nasser, Mona; Smith, Maureen; Thompson Coon, Jo; et al.
Abstract : Objective: To explore and map the findings of prior research priority-setting initiatives related to improving the health and well-being of older adults. Design: Scoping review. Data sources: Searched MEDLINE, EMBASE, AgeLine, CINAHL and PsycINFO databases from January 2014 to 26 April 2021, and the James Lind Alliance top 10 priorities. Eligibility criteria: We included primary studies reporting research priorities gathered from stakeholders that focused on ageing or the health of older adults (≥60 years). There were no restrictions by setting, but language was limited to English and French. Data extraction and synthesis: We used a modified Reporting Guideline for Priority Setting of Health Research (REPRISE) guideline to assess the transparency of the reported methods. Population–intervention–control–outcome (PICO) priorities were categorised according to their associated International Classification of Health Interventions (ICHI) and International Classification of Functioning (ICF) outcomes. Broad research topics were categorised thematically. Results: Sixty-four studies met our inclusion criteria. The studies gathered opinions from various stakeholder groups, including clinicians (n=56 studies) and older adults (n=35), and caregivers (n=24), with 75% of the initiatives involving multiple groups. None of the included priority-setting initiatives reported gathering opinions from stakeholders located in low-income or middle-income countries. Of the priorities extracted, 272 were identified as broad research topics, while 217 were identified as PICO priorities. PICO priorities that involved clinical outcomes (n=165 priorities) and interventions concerning health-related behaviours (n=59) were identified most often. Broad research topics on health services and systems were identified most often (n=60). Across all these included studies, the reporting of six REPRISE elements was deemed to be critically low. Conclusion: Future priority setting initiatives should focus on documenting a more detailed methodology with all initiatives eliciting opinions from caregivers and older adults to ensure priorities reflect the opinions of all key stakeholder groups.